Comparative characteristics of the physical training of women between 30 and 49 yearsof age based on indicators of physical training depending on the body weight fat component content - Salnikova, Svitlana; Сальникова, Cвітлана (Східноєвропейський національний університет ім.Лесі Українки, 2017)
The current relevance of the research. The paper is devoted to the research of fat body content influence on the parameters of physical state at 30-years women. It was determined that increasing of fat body content at 30–49 years women negatively affects speed, active spine flexibility, explosive strength, agility, power dynamic endurance of muscles of upper limb girdle and lower extremities, speed-power endurance of abdominal muscles, static fatigue of gluteal muscles and total endurance. Goal of research is to investigate the parameters of physical preparation of 30–49 years women depending on fat body content. Results of research: It is established the dependence between speed, active spine flexibility, explosive strength, agility, power dynamic endurance of muscles of upper limb girdle and lower extremities, speed-power endurance of abdominal muscles, static fatigue of gluteal muscles, total endurance and fat body content. The increasing fat body content at 30–36 years women leads to more negative effects compare to 37–49 years women. Conclusions. It is proved the reasonability of creation of special water fitness program for 30–49 years women. The purpose of such program is improving of physical qualities. Актуальність. У статті досліджено вплив умісту жирового компонента маси тіла на показники фізичної підготовленості в жінок 30–49 років. Установлено, що перевищення жирового компонента в жінок 30–49 років негативно вплинуло на прояв швидкості, активної гнучкості хребта, вибуховоїсили, спритності, силової динамічної витривалості м’язів плечового пояса й нижніх кінцівок, швидкісно-силової витривалості м’язів черевного преса, силової статичної витривалості сідничних м’язів та загальної витривалості. Завдання роботи –дослідити показники фізичної підготовленості жінок 30–49 років залежно від умісту жирового компонента маси тіла. Результати роботи. Установлено залежність прояву швидкості, активної гнучкості хребта, вибухової сили, спритності, силової динамічної витривалості м’язів плечового пояса й нижніх кінцівок, швидкісно-силової витривалості м’язів черевного преса, силової статичної витривалості сідничних м’язів і загальної витривалості від умісту жирового компонента. Перевищення вмісту жирового компонентавжінок30–36роківпризводитьдобільшнегативнихнаслідків,ніжу37–49-річних.Висновки.Доведена доцільність розробки програми занять аквафітнесом для жінок 30–49 років, спрямованих на покращення фізичних якостей, які зазнають найбільших інволюційних змін.
Порівняльна характеристика фізичного стану жінок 30–49 років за показниками фізичної підготовленості залежно від умісту жирового компонента маси тіла.
Keywords: physical preparation; physical qualities; makeup of body mass fat content; фізична підготовленість; фізичні якості; компонентний склад маси тіла; жировий компонент